Comparison of commingled and sequential production schemes by sensitivity analysis for Gulf of Mexico Paleogene Deepwater turbidite oil fields: A simulation study - Elnara Rustamzade; Wen Pan; John T. Foster; Michael Pyrcz (Energy Exploration & Exploitation, 2023)
A commingled production scheme, where wells are simultaneously completed in multiple reservoir units, offers a cost-effective alternative worldwide. However, their behavior can be more complex than single-unit wells in sequential production. Limited completion studies exist for the unique Paleogene Gulf of Mexico fields. To aid decision-making, we conducted a numerical study using geological and reservoir models of Lower and Upper Wilcox units, based on publicly available data. Results show that commingled production maximizes per-well oil production compared to sequential schemes. Over 30 years, it provides 61% more oil recovery, and over 50 years, it yields 21% more. One-factor-at-a-time design of experiments sensitivity analysis identifies that key reservoir properties influencing oil recovery in both schemes are upper and lower unit thicknesses, facies proportion of the upper unit. Additionally, average permeability of the lower unit plays a significant role in sequential production schemes.